Patterns of the present: from the perspective of Sri Aurobindo and the Mother - Vrekhem, Georges van (Rupa & Co., 2002)
Attempt to highlight the present situation of humanity in the perspective of the evolutionary vision of overman concept according to Aurobindo Ghose, 1872-1950, and the Mother, 1878-1973.